Terapi Okupasi dalam Mengatasi Kesulitan Memakai dan Melepaskan Kaos Kaki Pada Siswa Autis di SLB Anugerah Dimembe - Martince Palakua (Peneliti.net, 2020)
The purpose of this study was to obtain an overview of the effectiveness of occupational therapy in overcoming the difficulty of wearing and removing socks in Autistic Children at Anugerah Dimembe Special School. This research uses single subject research (single subject research) or SSR which is an experimental study that focuses more on individual scores or performance rather than group performance. The SSR design used is the A-B-A design. Data were collected for 30 days (1 month). The recording of target behavior data was carried out for 6 days for baseline conditions (A-1), 20 days for treatment conditions (B) and 3 days for baseline conditions (A-2). The results showed that the use of occupational therapy can improve the ability to wear and take off socks in children with autism, this can be achieved properly. With the achievement of a score that tends to be stable (score 4), it can be concluded that there has been a change or increase in the skills of children with autism in wearing and taking off socks. The results showed that autistic children after receiving treatment with occupational therapy were able to overcome the problem of wearing and removing socks, where in the initial condition the child was not able to do these activities. Although there have been many improvements, with the stages of occupational therapy, it is very helpful for teachers to be able to practice these skills.